Volemic loss in rapid maxilla expansion surgically assisted - Gaetti Jardim, Ellen Cristina; Faverani, Leonardo Perez; Okamoto, Roberta; Gaetti-Jardim Jr, Elerson; Shinohara, Elio Hitoshi (ARCHIVES OF HEALTH INVESTIGATION, 2016)
Surgeries for dentofacial deformity correction are procedures which are executed with considerable frequency nowadays and, due to their complexity concerning complications inherent to technique, such as arteriovenous lesions or even surgery time, may cause severe hypovolemia. Necessity of replacement of blood level through infusion of crystalloid solutions, colloids or even blood transfusion is always mandatory. This way, it is proposed in this study to quantify blood loss, as well as evaluate necessity of blood transfusion in 19 patients who underwent maxilla expansion. It was evaluated average arterial pressures, surgery procedure time, gender, volemic loss and ASA classification. Average blood loss was 296,84mL, with minimal value of 50mL and maximum 1000mL. We can conclude that hypovolemia and blood transfusion request in such surgeries was of small number, however, professionals should always be aware of surgical time and development of discerning surgical technique. Descriptors: Surgery; Hypovolemia; Blood Transfusion.